Evidences of World`s Technical Revolution 4.0 - Demchenko, Maxim; Udovik, I.M.; Zuyenok, I.I. (Видавництво НГУ, 2017)
Over last three centuries industry as it is now has dramatically changed and developed from global urbanization and steam machines to invention of PC with variety of digital devices and spreading of the Internet. The Fourth Industrial Revolution marked by emerging technology breakthroughs in a number of fields, including robotics, artificial intelligence, nanotechnology, biotechnology, the Internet of Things (IoT), 3D printing and autonomous vehicles. The Fourth Industrial Revolution was declared in Davos on “World Economic Forum” in 2016. This statement was built on the Digital Revolution, representing new ways in which technology becomes embedded within societies and even the human body.
Keywords: World`s Technical Revolution; мировая техническая революция